2019
DOI: 10.1007/s10964-019-01060-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use Subgroups Differentially Predict Psychosocial Well-Being During Early Adolescence

Abstract: Despite the salience of the social media context to psychosocial development, little is known about social media use patterns and how they relate to psychological and social functioning over time during early adolescence. This longitudinal study, therefore, identified subgroups of early adolescents based on their social media use and examined whether these subgroups predicted psychosocial functioning. Adolescents (N = 1205; 11-14 years; 51% female; 51% white) completed surveys at baseline and a six-month follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
109
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 85 publications
7
109
0
3
Order By: Relevance
“…Another potential explanation for the disparate findings is that the concept itself is broad, often vague, and measured differently. Some studies use well-being scales (Booker et al, 2018;, while others use general distress scales (Jensen et al, 2019) or examine symptoms of internalizing problems (Riehm et al, 2019), such as anxiety and depression (Boers et al, 2019;Coyne et al, 2020;Heffer et al, 2019;Vannucci and McCauley Ohannessian, 2019).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Another potential explanation for the disparate findings is that the concept itself is broad, often vague, and measured differently. Some studies use well-being scales (Booker et al, 2018;, while others use general distress scales (Jensen et al, 2019) or examine symptoms of internalizing problems (Riehm et al, 2019), such as anxiety and depression (Boers et al, 2019;Coyne et al, 2020;Heffer et al, 2019;Vannucci and McCauley Ohannessian, 2019).…”
mentioning
confidence: 99%
“…The few longitudinal studies on the topic have reported mixed findings. Some find that social media use predicts higher depressive symptoms (Boers et al, 2019;Vannucci and McCauley Ohannessian, 2019), panic disorder symptoms (Vannucci and McCauley Ohannessian, 2019), greater internalizing problems (Boers et al, 2019;Riehm et al, 2019) and worse well-being (Booker et al, 2018). However, others have found that frequency of social media use does not predict later mental health outcomes (Coyne et al, 2020;Jensen et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Social media provides researchers access to knowledge posted directly by users in near real time. Social media data have been utilized for infectious disease outbreak monitoring (16)(17)(18), adverse drug reaction detection (19,20), understanding behavioral health patterns (e.g., predicting depression) (21,22), and for characterizing prescription medication abuse/misuse (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%